ARID1A alterations function as a biomarker for longer progression-free survival after anti-PD-1/PD-L1 immunotherapy. Issue 1 (27th February 2020) - Okamura, Ryosuke; Kato, Shumei; Lee, Suzanna; Jimenez, Rebecca E; Sicklick, Jason K; Kurzrock, Razelle
Abstract : Background: Several cancer types harbor alterations in the gene encoding AT-Rich Interactive Domain-containing protein 1A (ARID1A), but there are no approved therapies to address these alterations. Recent studies have shown that ARID1A deficiency compromises mismatch repair proteins. Herein, we analyzed 3403 patients who had tumor tissue next-generation sequencing. Findings: Among nine cancer subtypes with >5% prevalence of ARID1A alterations, microsatellite instability-high as well as high tumor mutational burden was significantly more frequent in ARID1A -altered versus ARID1A wild-type tumors (20% vs 0.9%, p<0.001; and 26% vs 8.4%, p<0.001, respectively). Median progression-free survival (PFS) after checkpoint blockade immunotherapy was significantly longer in the patients with ARID1A -altered tumors (n=46) than in those with ARID1A wild-type tumors (n=329) (11 months vs 4 months, p=0.006). Also, multivariate analysis showed that ARID1A alterations predicted longer PFS after checkpoint blockade (HR (95% CI), 0.61 (0.39 to 0.94), p=0.02) and this result was independent of microsatellite instability or mutational burden; median overall survival time was also longer in ARID1A- altered versus wild-type tumors (31 months vs 20 months), but did not reach statistical significance (p=0.13). Conclusions: Our findings suggest that ARID1A alterations merit further exploration as a novel biomarker correlating with better outcomes after checkpoint blockade immunotherapy.